Recent developments in functionalized mesoporous materials for CO2 conversion - Arsh Ismaili; Gurwinder Singh; CI Sathish; Kavitha Ramadass; Vinay Naral; Stalin Joseph; Mercy Benzigar; Muhammad Ibrar Ahmed; Ajayan Vinu (Materials Today Catalysis)
Mesoporous materials are flourishing across every major research discipline, including carbon capture and conversion, energy storage, biomedical, photocatalysis, optics, and magnetics, and their promising potential has led to a flurry of publications. Among these applications, CO2 conversion using porous heterogeneous catalysts such as zeolites, clays, and mesoporous materials gained much attention in recent years as it has the potential to offer a solution for global warming. Although various porous catalysts have been used for CO2 conversion, mesoporous materials are particularly interesting owing to their large specific surface area, pore volume and pore diameter. These properties can be effectively utilized for creating unique catalytically active sites by loading metal or metal oxide species with high dispersion which are highly critical for efficient CO2 conversion. There have also been a significant number of reports on the direct use of mesoporous metal oxides, sulfides and/or phosphides, which exhibit appealing results for CO2 conversion as these inherently contain metal sites, and mesoporosity addition to them is an added advantage. Their continuous evolution warrants more sophisticated research to unveil their hidden properties by engaging in highly advanced characterization. The major emphasis of this review is to discuss various types of mesoporous materials mentioned above and their functionalized derivatives for CO2 conversion to mainly C1 products. The diverse range of mesoporous materials covered in this review will provide the readers with the opportunity to delve into their specific properties that control the efficiency of CO2 conversion.